2018
DOI: 10.1002/2017wr020471
|View full text |Cite
|
Sign up to set email alerts
|

Global Sensitivity of Simulated Water Balance Indicators Under Future Climate Change in the Colorado Basin

Abstract: The Colorado River Basin is a fundamentally important river for society, ecology, and energy in the United States. Streamflow estimates are often provided using modeling tools which rely on uncertain parameters; sensitivity analysis can help determine which parameters impact model results. Despite the fact that simulated flows respond to changing climate and vegetation in the basin, parameter sensitivity of the simulations under climate change has rarely been considered. In this study, we conduct a global sens… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 105 publications
(147 reference statements)
10
38
0
Order By: Relevance
“…The K parameter is the hydraulic conductivity when the soil moisture reaches saturation (Yang et al, 2014). The finding that streamflow is not sensitive to the K parameter is consistent with previous studies (Bennett et al, 2018;Demaria et al, 2007).…”
Section: 1029/2019wr025968supporting
confidence: 92%
See 2 more Smart Citations
“…The K parameter is the hydraulic conductivity when the soil moisture reaches saturation (Yang et al, 2014). The finding that streamflow is not sensitive to the K parameter is consistent with previous studies (Bennett et al, 2018;Demaria et al, 2007).…”
Section: 1029/2019wr025968supporting
confidence: 92%
“…For example, only 13 streamflow‐related soil parameter were involved in sensitivity analysis and optimization, and the effects of the vegetation parameters (e.g., LAI, albedo, roughness length, and canopy fraction) are not taken into account in this study. Previous studies have indicated that changes in runoff are sensitive to albedo (Bennett et at., ) and vegetation roots (Demaria et al, ) in the VIC model. Therefore, the optimal solution found by our automatic calibration framework is likely to be compensating for errors in some of the other vegetation parameters and model prediction uncertainty sources, including input data and structural uncertainties associated with the underlying model.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The sensitivity of model outputs to selected parameters is justified given the formulations of the variable infiltration and baseflow generation curve that form the foundation of the VIC architecture (Liang et al, , ) and as these parameters are traditionally applied in model calibration (i.e., Elsner et al, ). As reported in previous studies, sensitivity to these parameters hold in both current and future climate scenarios (Bennett et al, ; Christensen & Lettenmaier, ; Demaria et al, ). A previous effort used various objective functions and found that b inf and D2 were the most sensitive parameters followed by the drainage parameter among 10 VIC parameters across four American river basins of different hydroclimates (Demaria et al, ).…”
Section: Discussionsupporting
confidence: 67%
“…Projected changes to natural systems, particularly from climate, include shifts in temperature distributions, changes in the timing of streamflow extremes, and intensifying drought [11,12]. All of these impacts have significant consequences for large, managed river systems such as the Colorado River Basin (CRB).…”
Section: Introductionmentioning
confidence: 99%